Microscopic rigidity and heterogeneity of ionic liquids probed by stochastic molecular librations of the dissolved nitroxides. Issue 38 (20th September 2017) - Ivanov, Mikhail Yu.; Krumkacheva, Olesya A.; Dzuba, Sergei A.; Fedin, Matvey V.
Abstract : We propose a new potent approach for studying nano/microscopic heterogeneities in ionic liquids exploiting stochastic librations of nitroxides and pulse EPR. Abstract : Microscopic molecular organization and heterogeneities in ionic liquids (ILs) are of significant fundamental and applied interest. Although many theoretical studies have been dedicated to this topic, the development of experimental methods for studying such heterogeneities is still in demand. In this work we propose a new approach for the characterization of microscopic rigidity and heterogeneities in ILs using stochastic librations (small angle motions) of the nitroxide radicals as a probe. Stable nitroxides are dissolved in ILs, which are then shock-frozen and investigated using pulse Electron Paramagnetic Resonance (EPR) at variable temperatures. Stochastic molecular librations of nitroxides depend on local rigidity of a medium and manifest themselves in different electron dephasing times across the EPR spectrum. The use of advanced spiro-cyclohexane-substituted nitroxides allows implementation of this approach at temperatures up to ∼150 K and above. Remarkably, we have found that librational motions in ILs arise at much lower temperatures (∼75 K for [Bmim]BF4, [Bmim]PF6, [C10 mim]BF4 ) compared to common organic solvents. This can be rationalized by smaller local rigidity of the medium in ILs, most likely due to localization of nitroxides in low-density heterogeneities formed by non-polar alkyl chains. The structure, size, solubility and other properties of nitroxides are adjustable for particular tasks, therefore the proposed approach can potentially be implemented to probe the rigidity and heterogeneities of any ILs, thus providing vital insights into their molecular-scale self-organization.